Can Cementing Technique Reduce the Cost of a Primary Total Knee Arthroplasty? - Maheshwari, Aditya V.; Argawal, Mayank; Naziri, Qais; Pivec, Robert; Mont, Michael A.; Rasquinha, Vijay J. (The Journal of Knee Surgery, 2015)
Studies on cost containment of total knee arthroplasty (TKA) have generated substantial interest over the past decade. Although multiple studies have evaluated the various intraoperative methods to control cost, no prior study has evaluated the economic impact and the clinical outcome based on amount of bone cement needed for a primary TKA. At a minimum of 3 years follow-up, we observed no difference in implant survivorship or Knee Society scores, but did observe substantial cost savings when one versus two packets of bone cement were used in combination with a hand mixing technique. By eliminating several extra cement mixing products, we achieved an approximately $1,000 cost saving per case with no difference in clinical outcomes at midterm follow-up.
Keywords: TKA; arthroplasty; cement; cost/economic